The kill order (New York: Random House, Inc., 2013)
Sun flares have unleashed devastation on the earth. Mark and Trina were there when it happened, and against the odds they survived. But now a violent and highly contagious disease is spreading like wildfire. Worse still, it's mutating and people are going crazy. Mark and Trina will do anything to save their friends - if only they can avoid madness and stay alive...